Tunisia Economic Monitor, Winter 2021 : Economic Reforms to Navigate Out of the Crisis - World Bank (World Bank, Washington, DC, 2022)
The Economic Monitor examines four possible factors behind Tunisia’s slow recovery. First, the drop in mobility related to the pandemic may have been more harmful in Tunisia. However, mobility in Tunisia has dropped to a similar extent as other countries and it has now returned to pre-pandemic levels following the acceleration in the vaccination campaign since July. If anything, the mobility drop in Tunisia has resulted in a lower reduction in economic activity than in comparator countries as Algeria and Egypt. Second, it could be that the level of public support to the ailing firms and households may have been particularly low. However, at 2.3 percent of GDP, the Covid-19 stimulus package in 2020 was in the same ballpark as other comparators in the region. Third, the structure of the Tunisian economy, particularly its reliance on tourism, may have exposed it to the negative demand shock more than other countries. Indeed hotels, cafe and restaurant and transport are the sectors which have contracted the most since the start of the pandemic. The losses of these sectors explain a significant portion of the negative effects of the crisis in Tunisia, although they do not fully account for such slow recovery.